WAYS TO INCREASE THE PERFORMANCE OF CHISEL-CULTIVATORS AND REDUCE ENERGY CONSUMPTION - M. T. Mansurov; B. U. Toshpolatov; O.N. Toshpolatov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Pre-sowing tillage occupies an important place among agrotechnical measures for high yield of cotton and other agricultural crops. The main task is to soften the land to a specified depth, to create a soft soil layer on the surface of the field, to level it and to compact it to the required level, to preserve the moisture accumulated in the fields in autumn-winter and early spring, to eliminate germinating weeds and, most importantly, to remove seeds and other seeds. is to create conditions for uniform sowing and harvesting.